PENGENALAN PROSES PEMISAHAN KOMPONEN MINYAK ATSIRI KE SMA BAHRUL MAGHFIROH, MALANG - Aji Hendra Sarosa; Vivi Nurhadianty; Luthfi Kurnia Dewi; Wa Ode Cakra Nirwana; Safrina Hapsari; Ardian Indra Bayu; Rifa Rahma Andriana (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Bahrul Maghfiroh High School (SMA BM) as an educational institution wishes to develop knowledge in the exact field. The existence of the Merdeka curriculum encourages students to be able to develop their potential according to their talents and interests. The team has various experiences in isolating and separating essential oil components, including separating citronella oil components by evaporation or fractionation, isolating kaffir lime leaf oil components, and others. This service focuses on providing knowledge to SMA BM students in isolating and separating essential oil components. The purpose of this service is SMA BM students have experience in isolating and separating essential oil components and can support the achievements of SMA BM students by adding new knowledge. The implementation of this service includes providing the basics of separating essential oil components, training on laboratory-scale separation, visiting the Institut Atsiri mini plant in Ngijo to see the equipment for separating essential oil components (fractionation), and monitoring. The achievement of implementing this community service activity can be seen from student satisfaction with the results of the questionnaire, namely an average satisfaction of around 36% answered strongly agree, 48% answered agree and the satisfaction index value ranged from 78.75 (good). Therefore, service activities need to be carried out continuously and can be developed to provide good knowledge. Abstrak SMA Bahrul Maghfiroh sebagai institusi Pendidikan berkeinginan mengembangkan pengetahuan dalam bidang eksakta. Adanya kurikulum Merdeka, mendorong siswa untuk dapat mengembangkan potensi yang dimiliki sesuai dengan bakat dan minatnya. Tim pengabdian memiliki berbagai pengalaman dalam mengisolasi dan memisahkan komponen minyak atsiri antara lain pemisahan komponen minyak sereh wangi dengan evaporasi atau fraksinasi, mengisolasi komponen minyak daun jeruk purut, dan lain-lain. Pengabdian ini berfokus dalam memberikan pengetahuan kepada siswa-siswi SMA BM dalam mengisolasi dan memisahkan komponen minyak atsiri. Tujuan pengabdian ini agar siswa-siswa SMA BM dapat memiliki pengalaman dalam mengisolasi dan memisahkan komponen minyak atsiri, serta dapat menunjang prestasi siswa-siswi SMA BM dengan menambah pengetahuan baru di bidang eksakta. Pelaksanaan pengabdian meliputi pemberian materi dasar-dasar pemisahan komponen minyak, pelatihan pemisahan minyak atsiri skala laboratorium, kunjungan ke mini plant Institut Atsiri di Ngijo untuk melihat peralatan pemisahan komponen minyak atsiri (fraksinasi), dan monitoring. Ketercapaian pelaksanaan kegiatan pengabdian masyarakat ini dilihat dari kepuasan mahasiswa terhadap hasil angket yaitu rata-rata kepuasan sekitar 36% menjawab sangat setuju, 48% menjawab setuju dan nilai indeks kepuasan berkisar 78,75 (baik). Oleh karena itu, kegiatan pengabdian perlu dilakukan secara kontinyu dan bisa dikembangkan untuk pemberian pengetahuan yang baik.